Spatial variability of the physical and mineralogical properties of the soil from the areas with variation in landscape shapes - Souza, Zigomar Menezes de; Marques Júnior, José [UNESP]; Pereira, Gener Tadeu [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Este trabalho teve como objetivo avaliar a influência das formas do relevo na variabilidade espacial de atributos físicos e suas relações com a mineralogia da argila de um Latossolo Vermelho eutroférrico, utilizando a técnica da geoestatística. Os solos foram amostrados nos pontos de cruzamento de uma malha, com intervalos regulares de 10 m, nas profundidades de 0,0-0,2 m, 0,2-0,4 m e 0,4-0,6 m para os atributos físicos e 0,6-0,8 m para os atributos mineralógicos. Os valores médios para a densidade do solo e resistência do solo à penetração são maiores no compartimento I onde a relação Ct/Ct+Gb é relativamente maior, indicando a presença de maior teor de caulinita. No compartimento II a condutividade hidráulica e a macroporsidade são maiores, influenciados provavelmente pelo predomínio da gibbsita. Portanto, conclui-se que a identificação das pedoformas é muito eficiente para compreender a variabilidade espacial de propriedades do solo. Sendo que, as variações na forma da paisagem promovem variabilidade espacial diferenciada das propriedades físicas e mineralógicas do solo.

The objective of this work it was to use the geostatistics methods to investigate the spatial relationships between the physical and mineralogical properties of an oxisol planted with the sugarcane in an area of slight variations in the landform. The soil was sampled at 10 m regular intervals in the crossing points of a 100 x 100 m grid. At each point, the soil was collected at 0.0-0.2 m, 0.2-0.4 m and 0.4-0.6 m depths for the analyzes of physical properties and at 0.6-0.8 m for the mineralogical analyses. Both the Kt/Kt+Gb ratio and Kt relative crystallization level were higher in the compartment I than in the compartment II. As a consequence, the soil penetration resistance and bulk density were higher in the compartment I, while the macroporosity and Ksat were lower. Therefore, it was concluded that both the identification and mapping of a landform were efficient for understanding the spatial variability of the soil properties. Moreover, variations in the landscape shape promoted the differentiated variability of the physical and mineralogical soil properties: the more variable the landscape, the more variable was the soil properties.
Keywords: Sugarcane; Geostatistics; soil-landscape relationship